2004
DOI: 10.1182/blood-2003-04-1098
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo depletion of alloreactive cells based on CFSE dye dilution, activation antigen selection, and dendritic cell stimulation

Abstract: Eliminating alloreactive cells from T-cell populations would enable the transfer of immune function to patients who receive stem cell transplants. However, highefficiency depletion has proved difficult to achieve. We sought to develop ex vivo approaches for the maximal depletion of alloreactive CD4 ؉ T cells. Using a flow cytometric cell sorting approach after mixed lymphocyte reaction (MLR) culture, we have found that sorted CFSE bright (5-(and-6)-carboxyfluorescein diacetate succinmidyl ester) (nondivided) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 36 publications
2
73
0
Order By: Relevance
“…In situations of human, and mice MHC II mismatch, it has been reported that the precursor frequency of alloreactive effectors CD4 T lymphocytes causing host aGVHD is around 5%. 39 Our murine model of aGVHD, which involves a mismatch in both MHC I and MHC II might result in a similar precursor frequency in both CD4 and CD8 T lymphocytes. Such a 5% frequency would correspond to 5 Â 10 6 precursors of alloreactive effectors cells in the 10 8 allogeneic lymphocytes that we injected into the immunodeficient SCID recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In situations of human, and mice MHC II mismatch, it has been reported that the precursor frequency of alloreactive effectors CD4 T lymphocytes causing host aGVHD is around 5%. 39 Our murine model of aGVHD, which involves a mismatch in both MHC I and MHC II might result in a similar precursor frequency in both CD4 and CD8 T lymphocytes. Such a 5% frequency would correspond to 5 Â 10 6 precursors of alloreactive effectors cells in the 10 8 allogeneic lymphocytes that we injected into the immunodeficient SCID recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Most have used modified MLCs and have included deletional Abs or immunotoxins against activation markers (32)(33)(34), enhancement of activation-induced cell death in the alloreactive population (35), magnetic bead sorting to remove cells expressing activation markers such as CD69 or CD25 (36 -38), cell sorting by flow cytometry based on cell size and activation markers (39), viral infection of stimulator cells to enhance activation in the MLC (40), and keratinocytes as stimulator cells (41). Most recently, the use of CFSE to remove alloreactive T cells has been shown in BMT to reduce GVHD (42). The removal of a specific alloreactive population has been tried experimentally in the graft-vs-host model and in an allograft model using a suicide gene (43).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these approaches use a common mechanistic platform of ex vivo donor T-cell stimulation by recipient alloantigens and subsequent removal or destruction of alloreactive T cells, identified by expression of activation markers, proliferation, or metabolic activity. [8][9][10][11][12] An alternative to selective allodepletion is induction of allospecific anergy (hyporesponsiveness to subsequent restimulation with alloantigens) in donor T cells before HSCT. T cells require at least 2 signals to become activated: cognate antigen/ MHC binding to the T-cell receptor (signal 1) and positive costimulatory signals from antigen presenting cells (APCs; signal 2).…”
Section: Introductionmentioning
confidence: 99%